Exploration and Practice of New HSS Construction in the Public Affairs Administration Major of Medical Colleges: An example of Southwest Medical University - Weili Hu, Xue Sun (Forest Chemicals Review, 2021)
The new humanities and social sciences construction is an important part of the current higher education reform in China. It is an exploratory reform in the field of humanities and social sciences in the sense of adapting to the national strategic development and responding to the scientific and technological revolution. Taking the opportunity of the new humanities and social sciences construction, the major of public affairs administration in Southwest Medical University upgraded the concept, mode, content and means of personnel training, gave full play to the platform advantages of medical colleges, realized the deep integration of medicine and management, explored and constructed a new HSS construction program that integrates the three systems of “talent training, teacher workforce and quality culture”, which is expected to provide reference for the advancement of higher education reform.